2011
DOI: 10.1590/s0100-69162011000500002
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of automated acclimatization during the pre-milking phase of lactating girolando cows

Abstract: ABSTRACT:The aim of this paper was to evaluate the automated acclimatization effects during pre-milking of cows on thermal conditioning, physiology, milk production and cost-benefit of the automated adiabatic evaporative cooling system (AECS). The treatments 20; 30; 40 min and control consisted of exposure time of pre-milking cows to the automated AECS. Sixteen cows were used with an average daily milk yield of 19 kg, distributed in a 4 x 4 Latin square design. The Tukey's test (P<0.05) was used to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(17 reference statements)
0
4
0
4
Order By: Relevance
“…Almeida et al (2010), assessing a holding penclimatization system by misting, obtained a time of 58 days for return on investment. Silva et al (2011), in turn,observed a better result with 40 minutes of misting climatization, reporting 43 days for return on investment.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Almeida et al (2010), assessing a holding penclimatization system by misting, obtained a time of 58 days for return on investment. Silva et al (2011), in turn,observed a better result with 40 minutes of misting climatization, reporting 43 days for return on investment.…”
Section: Resultsmentioning
confidence: 90%
“…Silva, Pandorfi, Almeida, Guiselini and Henrique (2011) verified a 3.66% increase in milk production as of the implementation of a climatization system with shading, ventilation and water sprinkling. Almeida, Pandorfi, Guiselini, Almeida and Morril (2010), in their turn, found an increase of 4.35% in the milk production of cows subjected to climatization with a similar system.…”
Section: Introductionmentioning
confidence: 86%
“…A climatização por 30 min apresentou redução significativa (P < 0,05), quando comparada com a de 10 min; mas todas as condições de alojamento estiveram abaixo do valor considerado crítico (ITU < 75) para vacas 7/8 Holandês-Gir (Azevedo et al, 2005). Os resultados apontados no turno da tarde estão abaixo daqueles observados por Silva et al (2011) que verificaram, às 14 h, valores de 78,6; 74,9; 74,4 e 74,1, para o curral de espera sem climatização, 20, 30 e 40 min de climatização, com acionamento automatizado.…”
Section: Resultsunclassified
“…Resultados semelhantes foram obtidos por Silva et al (2011) que verificaram redução na FR de 75,7 para 34,0 mov min -1 , para vacas lactantes da raça Girolando, que tiveram acesso ao curral de espera equipado com SRAE, durante 40 min de exposição, no verão do semiárido pernambucano.…”
Section: Resultsunclassified
“…Sprinkling system was composed of a PVC line of 25 mm and six rotating microsprinklers with a 1.2-mm nozzle, average flow rate of 66 L h −1 , and the distance between nozzles of 2.40 m. The climatization system was turned on only when the air or dry bulb temperature was higher than 26 °C, as recommended by Silva et al (2011).…”
Section: Methodsmentioning
confidence: 99%